Static hot-fire testing of a green hybrid rocket engine - Ahmad, Mohamed Tarmizi; Jagannathan, Anudiipnath; Abidin, Razali; Zhahir, Amzari; Saniman, Muhammad Nur Farhan (Aeronautical and Astronautical Society of the Republic of China, 2014)
This paper presents the conduct of the hot-fire testing for a green hybrid rocket engine. The hybrid rocket engine consists of liquid nitrous oxide (N2O) as the oxidizer, with the stearic acid as the solid fuel and the incorporation of carbon nanotube and aluminum powder as the additives. From the conducted experimental, all systems that have been designed and developed in this study for the green hybrid rocket engine are demonstrated to be successful and fully functional, which also include the radio frequency control unit. Based on the results of the experiment, the developed laboratory-scale green hybrid rocket motor has been successfully ignited and produced a maximum thrust of 348 N, with the maximum combustion chamber pressure is recorded as 14 bar. In addition, several suggestions to improve the hybrid rocket engine design are also discussed.